Rocky Mountain Bird Observatory: stewardship, education, science - Gallagher, Seth, speaker; Morgan, Ken, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Originating in 1999 as Prairie Partners, the program was to address declining bird trends on a landscape used for agricultural production. Private landowners own or manage a considerable percentage of this land. Their involvement in conservation efforts is essential to the future of grassland and sagebrush birds. The mission of the program is to coordinate voluntary, cooperative partnerships with landowners to address the management of declining bird species and other resource conservation issues. In 2003 Stewardship began working with landowners and resource agencies to implement on-the-ground habitat projects. These projects include stream-bank restoration, shallow water restoration, woody-invasive species control, prescribed burning, restoration of native vegetation, fence marking and rotational grazing.
Rocky Mountain Bird Observatory stewardship program
Moderator: Ken Morgan.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses